Differential Expression of Ribosomal Genes in Brain and Blood of Alzheimer's Disease Patients - Rasmussen, Lucas; Labio, Roger W. de; Viani, Gustavo A.; Chen, Elizabeth; Villares, Joao; Bertolucci, Paulo-Henrique; Minett, Thais S.; Turecki, Gustavo; Cecyre, Danielle; Drigo, Sandra A. [UNESP]; Smith, Marilia C.; Payao, Spencer L. M. (Bentham Science Publ Ltd, 2015)
Changes in rRNA and rDNA expression have been associated with cellular and organism aging and have been linked to Alzheimer's disease (AD) pathogenesis. In this study, we investigated the mRNA expression of ribosomal genes (28S/18S) and beta-amyloid precursor protein (APP) in different post mortem brain tissue regions (the entorhinal and auditory cortices and the hippocampus) of AD patients and elderly control subjects and also evaluated the extent of expression in peripheral blood from young, healthy, elderly, and Alzheimer's disease patients in order to investigate whether these individuals experienced the effects of aging. The comparative threshold cycle (CT) method via Real Time Polymerase Chain Reaction and the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) were used to analyze gene expression and the Apolipoprotein E (APOE) genotype, respectively. When the brain areas were analyzed collectively, we observed a significant decrease in APP expression and a significant increase in levels of mRNA of 18S and 28S in Alzheimer's disease patients compared to healthy elderly individuals. Furthermore, there was a significant upregulation of 28SrRNA in the entorhinal cortex and hippocampus, but not in the auditory cortex of patients with AD. On the other hand, tests of blood samples verified a decreased expression of 28S rRNA in patients with AD. These results support the hypothesis that changes in rRNA are present in AD patients, are tissue-specific, and seem to occur independently and differently in each tissue. However, the next challenge is to discover the mechanisms responsible for the differences in expression observed in the blood and the brain in both healthy elderly individuals and Alzheimer's disease patients, as well as the impact of these genes on AD pathogenesis.
Keywords: Alzheimer's disease; brain; blood; ribosomal genes; 18S; 28S